Death at the Opposite Ends of the Eurasian Continent Mortality Trends in Taiwan and the Netherlands 1850-1945 - Engelen, Theo; Shephard, John R.; Wen-shan, Yang (Life at the Extremes, 2011)
This volume examines contrasting historical demographics in Western Europe and Asia, taking the Netherlands and Taiwan as representative populations. Both countries have witnessed steady, continuous improvements in public health, disease prevention, and medical care. The contributors compare the impact of disease and mortality on the lives of individuals and families under very different cultural and social conditions. Death at the Opposite Ends of the Eurasian Continent analyzes a variety of factors, including maternal and infant mortality, as well as the accuracy of Taiwan's censuses and death reporting.